Identification of Types of Characters Built in the Implementation of Mukemel Culture in the School Environment - Sanofa, Edi; Najmuddin, Najmuddin; Rahmi Novalita, Rahmi Novalita (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to identify the character that is built in the implementation of mukemel culture. The research setting was carried out at State Elementary School 04 Jagong Jeget, State Elementary School 06 Jagong Jeget and State Elementary School 16 Pegasing, Central Aceh Regency. The reason for choosing the research location was because the school had implemented mukemel culture as a school culture in building student character. The informants in this research were key informants, namely the school principal, teachers and students. The technique for taking informants uses the snowball sampling technique. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data display, and drawing conclusions. The results of the research show that the types of character built in the application of mukemel culture are religious, responsible, peace-loving, honest, creative, democratic, hard working, disciplined. The cultural system of the Gayo community basically contains knowledge, beliefs, values, religion, norms, rules and laws which become a reference for students in behaving through the application of regional culture in the school environment.